Effects of transcutaneous electrical stimulation with the device “VEB” ® on the human body - Babelyuk, Valeriy; Babelyuk, Nazariy; Popovych, Igor; Gozhenko, Anatoliy; Kyrylenko, Iryna; Korolyshyn, Tetyana; Dubkova, Galyna; Kovbasnyuk, Marta; Hubyts’kyi, Victor; Kikhtan, Volodymyr; Musiyenko, Vira; Dobrovolsky, Yuriy; et al. (Journal of Education, Health and Sport, 2022)
Background. In 2015, a generator for electrotherapy and stimulation oh human nerve centers was created, called “VEB-1”®. Preliminary observation of volunteers revealed a modulating effect of a four-day course of electrical stimulation on the parameters of electroencephalogram, metabolism, as well as gas-discharge visualization (GDV). In this message, we present the results of the approbation of the device on an expanded contingent of volunteers with the use of additional research methods and a new modification of the device. Material and research methods. The object of observation were employees of the sanatorium “Moldova”, patients with chronic cholecystitis: 19 women 30-62 y and 19 men 25-63 y. In the morning registered HRV (“CardioLab+HRV”, “KhAI-Medica”, Kharkiv, UA), EEG (“NeuroCom Standard”, “KhAI-Medica”, Kharkiv, UA), kirlianogram by the method of GDV (“GDV Chamber”, “Biotechprogress”, SPb, RF), electroconductivity of skin in three pairs of points of acupuncture (“Medissa”), electrokinetic index of buccal epithelium ("Biotest", Kharkiv State University), as well as some endocrine, immune and metabolic parameters. After the initial testing, an transcutaneous electrical stimulation session was performed with a “VEB-1”® or a “VEB-2” devices. The next morning after completing the four-day course, retesting was performed. Results. Electrical stimulation causes a sympathotonic shift in the sympatho-vagal balance and an increase in PSD of delta-rhythm generating neurons combined with a decrease in PSD of beta- and theta-rhythm generating neurons. This is accompanied by increase in phagocytosis and favorable changes in immune, biochemical and biophysical parameters as well as increase in testosterone level in men only. The integral effects on the constellation of registered body parameters of both device modifications do not differ significantly. Conclusion. The "VEB" device exerts an adaptogenic effect on the body through transcutaneous electrical stimulation of neurons.